Legal nature of the Agency in Legal system of the Republic of Serbia - Martinović, Aleksandar (Zbornik radova Pravnog fakulteta u Novom Sadu, 2012)
The roots of the agency as a public law, go back to the nineteenth century, when the first independent regulatory agency - Interstate Trade Commission was formed by the United States. In the legal system of the Republic of Serbia, agencies have the right to acquire citizenship since 2001. In the past ten years, a very large number of agencies were formed in different areas of social life, with their different legal nature. Disparity in legal character agency in the Republic of Serbia in general raises no small problems. The economic and financial characteristics of agencies are expressed  especially  in situations when a same social area "covered" simultaneously by the relevant ministry and its counterpart - the agency.